Effects of Azulene on Granulation Tissue Formation and Epithelialization during Skin Wound Healing in BALB/c Mice - Mohammad Afshar; Mohammad mehdi Hassanzadeh-Taheri; Mahmood Zardast; Faezeh Vahdati (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Azulene is a non-alternating hydrocarbon with various biological activities including anti-inflammatory activity. This study investigated the effects of azulene on granulation tissue formation and epithelialization in skin wound healing in mice. Materials and methods: In this experimental study, 60 adult male BALB/c mice were divided into 5 groups (n=12): experimental groups I and II were treated with 1% and 2% azulene, respectively and groups III and IV were treated with nitrofurazone and ucerin cream, respectively. Group V did not receive any treatment. After deep anesthesia, a linear wound (2 cm length) was made on dorsal thoracic skin of the mice. Then, wound samples were taken at days 4, 7, 10, and 14 after treatments and processed for histological and microscopic examinations using Hematoxiline-Eosin (H&E) and Masson Trichrome staining methods. Data analysis was done in SPSS V24 applying One-way ANOVA and Tukey test. Results: The means of granulation formation, angiogenesis, fibroblast cells, and collagen formation increased significantly in groups I and II at days 7, 10, and 14 compared to those of the negative control and sham groups (P<0.01). Also, the rate of epithelialization was higher in these groups compared with that of other groups (P<0.05). Conclusion: In current study, azulene could accelerate skin wound healing in BALB/c mice.